A triptycene derived hypercrosslinked polymer for gas capture and separation applications. Issue 1 (28th July 2021) - Ansari, Mosim; Bera, Ranajit; Das, Neeladri
Abstract: This work describes facile synthesis of a porous polymeric material (T‐HCP ) using readily available reagents. Specifically, T‐HCP is a thermally stable and hypercrosslinked polymer (HCP) that is essentially microporous with a high BET specific surface area (940 m 2 g −1 ). Triptycene based polymers are known to feature internal free volume. Thus, the incorporation of triptycene units and extensive crosslinking by an external cross‐linker in T‐HCP makes it a promising adsorbent for small gas capture applications. Experimental results show that T‐HCP demonstrated good CO2 capture capacity of 132 mg g −1 (273 K, 1 bar). Molecular hydrogen storage capacity of T‐HCP is estimated to be 17.7 mg g −1 (77 K, 1 bar). T‐HCP revealed high CO2 /N2 selectivity (up to 63) as well as promising CO2 /CH4 (up to 9.1) selectivity suggesting its potential applicability for CO2 separation from flue and natural gases. Abstract : A one‐pot and facile synthesis of a new triptycene‐based hypercrosslinked polymeric network (via knitting strategy) with high BET specific surface area (940 m 2 g ‐1 ) and demonstrating high CO2 capture capacity (132 mg g ‐ 1 at 273 K, 1 bar), high CO2 /N2 selectivity and reasonable uptake of H 2 at 77 K.